Asymmetric Divergence in Transmitted SNPs of DNA Replication/Transcription and Their Impact on Gene Expression in Polyploid Brassica napus - Tang, Minqiang; Li, Juanling; Hu, Xu; Sun, Lu; Helal, MMU; Chen, Jianguo; Zhang, Yuanyuan (Frontiers in Genetics, 2021)
The marked increase in plant genomic data has provided valuable resources for investigating the dynamic evolution of duplicate genes in polyploidy. Brassica napus is an ideal model species for investigating polyploid genome evolution. The present study comprehensively analyzed DNA and RNA variation of two representative B. napus inbredlines, Zhongshuang11 and Zhongyou821, and we investigated gene expression levels of An and Cn subgenomes in multiple tissues of these two samples. The distribution of transmitted single nucleotide polymorphisms (SNPs) was significantly different in two subgenomes of B. napus. Gene expression levels were significantly negatively correlated with number of variations in replication and transcription of the corresponding genes, but were positively correlated with the ratios of transmitted SNPs from DNA to RNA. We found a higher density of variations in An than in Cn in SNPs during DNA replication and found that more SNPs were transmitted to RNA during transcription, which may contribute to An expression dominance. These activities resulted in asymmetrical gene expression in polyploid B. napus. The SNPs transmitted from DNA to RNA could be an important complement feature in comparative genomics, and they may play important roles in asymmetrical genome evolution in polyploidy.